2022
DOI: 10.3390/en15124454
|View full text |Cite
|
Sign up to set email alerts
|

Novel PEV Charging Approaches for Extending Transformer Life

Abstract: The study investigates how variable rate charging can affect PEV charging and identifies how this capability can be integrated into residential neighborhoods. The results show that creating PEV chargers that can deliver variable rates will enhance uncontrolled and controlled PEV charging. The integration is summarized into 4 phases. In phase 1, uncontrolled PEV chargers should be enabled to provide any rate to vehicles within 0 to 11.5 kW, which can reduce overloading by up to 28.34%. Phase 2 introduces smart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…They adopt vehicles of 16 kWh and 24 kWh charging at 3.3 kW and 6.6 kW. Reference [9] proposes a smart charging algorithm with variable-rate to mitigate transformer overloading and loss-of-life. The method is compared with other strategies, such as uncontrolled charging and fixed-rate controlled charging, with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…They adopt vehicles of 16 kWh and 24 kWh charging at 3.3 kW and 6.6 kW. Reference [9] proposes a smart charging algorithm with variable-rate to mitigate transformer overloading and loss-of-life. The method is compared with other strategies, such as uncontrolled charging and fixed-rate controlled charging, with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that with a high penetration of EVs, and no support from photovoltaic (PV) and ES, the transformers will dramatically age. Furthermore, researchers have dealt with the influence of the charging method on transformers' aging [8][9][10][11][12][13]. The main idea is to find an optimal charging scheme to minimize the impact of EVs' charging demand on distribution transformers.…”
Section: Introductionmentioning
confidence: 99%
“…In one paper [10], a simple method is used to coordinate the charging process of PEVs to avoid the overloading of transformers by using the fact that idle time represents a significant percentage of EV parking time. In the paper, [11] reducing the impact on transformer aging by implementing the capability of delivering a variable charging rate has been proposed. Two charging algorithms have been used as strategic ways for reducing the overload of distribution transformers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the charging problem of PEVs has been extensively studied [5][6][7][8][9][10]. In these studies, the electrical-energy-related aspects of the PEV charging problem are managed through different aspects.…”
Section: Introductionmentioning
confidence: 99%